Sustentabilidade em empreendimentos autogestionários no Brasil: análise de duas experiências no ramo têxtil em São Paulo e Minas Gerais - Dias, Marcos de Carvalho (Universidade Federal de São Carlos, 2011)
The self-management enterprises represent in Brazil, especially in the 80 s and 90 s, an alternative to workers who lost their jobs due to closure of businesses in this period, a result of the new foreign trade policies adopted by the federal government. Such enterprises, which are organized in the form of commercial companies or civil self-managed, have brought important individual and collective benefits, including job creation and income. However, the main feature of this type of development is related to its sustainability, or the possibility of maintaining a perennial way as an alternative to the conventional production, because they must not only meet the current needs of their members, but also future ones. But the relations of these enterprises with their own socio-labor relations are different from conventional business and thus the sustainability of these enterprises should be treated differently when compared to conventional developments due to its peculiarities in relation the form of production organization and labor relations. Therefore, this thesis aims to analyze the sustainability of projects, considering the specifics of these, through the theoretical approach to the subject and study of two cases arising from new developments bankrupt textile companies, and noted that such enterprises have different results in terms of performance production and revenues, despite serving in the same market and are subject to the same level playing field (so the market conditions do not represent a factor that directly influences the sustainability of self-management enterprises). In both there was a lack of adoption of a new technical base to produce specific self-management, as well as an educational policy aimed at selfmanagement principles and production organized collectively by the workers. It is also notable in these developments the absence of effective relations of partnership with other cooperative enterprises or joint production chain. As for the elements perceived differently in the projects, there are links in one of participation, cooperation, democracy and accountability in the domestic sphere of production and labor relations, which are perceived poorly in another venture, which has hurt the organization production and work. We concluded that the elements that make up the principles of self-managed production, the effective participation of its members in the cooperative management of a democratic, cooperation in the production environment and collective responsibility over the fate of the enterprise are explanatory factors of sustainability in self managed enterprises.
Keywords: Autogestão no trabalho; Sustentabilidade; Indústria têxtil; Self management; Sustainability; Textile industry; ENGENHARIAS::ENGENHARIA DE PRODUCAO